MENINGKATKAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN EXPLICIT INSTRUCTIONPADA MATA PELAJARAN IPA DI KELAS V SD NEGERI 104208 CINTA RAKYAT (JURNAL HANDAYANI PGSD FIP UNIMED, 2017)
Abstract: Improving Student Learning Outcomes Using Learning Model Explicit Instruction In Subject Science IPA in Class V State Element 104208 Cinta Rakyat. Method of this research is Classroom Action Research (PTK) apply two cycles that is cycle I and II.Berdasarkan research done In the first cycle obtained an average value increased to 63.87, students who complete learning there are 17 students and the percentage of student learning outcomes classically 54.84%